MENINGKATKAN PERCAYA DIRI KONSELI MELALUI PENDEKATAN BEHAVIOURISTIK TEKNIK POSITIVE REINFORCEMENT: Meningkatkan Percaya Diri Konseli Melalui Pendekatan Behaviouristik Teknik Positive Reinforcement - Ahmad Jumanto; Indah Lestari (STKIP PGRI SUMENEP, 2023)
The counselee's confident behavior is decreasing day by day due to pressure from outside and from within which makes the counselee increasingly think unworthy. The method used in this research is a case study in which data collection uses interview and observation techniques. the implementation of individual counseling in the context of increasing self-confident behavior in counselees using a behavior approach with positive reinforcement techniques is very effective because carrying out 2 meetings can have a positive effect on counselees by wanting to change their behavior to be brave in taking on various things